Health and growth of Finnish beef calves and the relation to acute phase response - Seppä-Lassila, Leena (Livest Sci, 2017)
Healthy, thriving calves are essential for beef calf production. We studied the health status and factors associated with the growth of beef calves in six cow-calf herds during the first month of the calves’ lives and at weaning age (200 days). The six herds were visited three times, when calves were approximately 3 days, 16 days and 30 days of age. On each visit calves (n=37) were clinically examined, weighed or measured, blood samples were collected, faecal samples obtained and deep nasopharyngeal swabs were taken. Each blood sample was analysed for acute phase proteins (haptoglobin, serum amyloid-A, fibrinogen), total proteins and albumin, the faecal sample for intestinal tract pathogens (rotavirus, bovine coronavirus, enterotoxigenic Escherichia coli and Salmonella, oocysts of Eimeria coccidia and Cryptosporidium, and nematode eggs), and the nasopharyngeal swab for respiratory tract pathogens (bovine coronavirus (BCV), respiratory syncytial virus (RSV), bacteria and mycoplasma). Clinical diagnosis of respiratory tract disease, diarrhoea or umbilical disease was set at 15.0% for all the three consecutive examinations combined (n=107), but only few pathogens were detected from the samples. The increased levels of acute phase proteins were neither associated with any of the diseases nor with the pathogens. Random intercept linear models were used to explore factors affecting early (3–30 days) and long-term (3–200 days) growth, showing that calves with elevated serum amyloid-A concentrations at the age of 16 days had lower long-term growth. Increased albumin concentration at 30 days of age and higher parity of the dam increased early-term growth. The lack of association between a disease and the acute phase protein may stem from the low disease prevalence in the beef calves examined. The measurement of acute phase proteins of a young calf can help identify animals with possible future growth deficiencies, although the mechanisms through which the association between acute phase proteins and growth has yet to be explained.